2000
DOI: 10.1074/jbc.275.16.11610
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Dynamin I on Ser-795 by Protein Kinase C Blocks Its Association with Phospholipids

Abstract: Dynamin I is phosphorylated in nerve terminals exclusively in the cytosolic compartment and in vitro by protein kinase C (PKC). Dephosphorylation is required for synaptic vesicle retrieval, suggesting that its phosphorylation affects its subcellular localization. An in vitro phospholipid binding assay was established that prevents lipid vesiculation and dynamin lipid insertion into the lipid. Dynamin I bound the phospholipid in a concentration-dependent and saturable manner, with an apparent affinity of 230 ؎ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 55 publications
(56 reference statements)
3
63
0
Order By: Relevance
“…Experiments demonstrating the interaction of p85␣ subunit of PI 3-kinase with dynamin have been performed in vitro (39,42). Our data further indicate that such interaction also occurs in intact cells and is enhanced in response to GPCR signals.…”
Section: Dynamin-2 and Na ϩ K ϩ -Atpase Endocytosismentioning
confidence: 60%
See 3 more Smart Citations
“…Experiments demonstrating the interaction of p85␣ subunit of PI 3-kinase with dynamin have been performed in vitro (39,42). Our data further indicate that such interaction also occurs in intact cells and is enhanced in response to GPCR signals.…”
Section: Dynamin-2 and Na ϩ K ϩ -Atpase Endocytosismentioning
confidence: 60%
“…Most studies have indicated that dyn1 is a substrate for PKC. Phosphorylation of dyn1 occurs at Ser 795 , and this effect also blocks its association to phospholipids (39). Using specific dyn2 and phosphoserine antibodies, our results suggest that dyn2 is also a good phosphosubstrate, most likely for PKC.…”
Section: Dynamin-2 and Na ϩ K ϩ -Atpase Endocytosismentioning
confidence: 73%
See 2 more Smart Citations
“…For example, a candidate in mediating Dyn2 function at the EDS might be cortactin, a tyrosine-phosphorylated cortical actin-binding protein proposed to play a role in tumor cell invasion (reviewed in Weed and Parsons, 2001), and also known to 1) mediate the regulatory function of dynamin on actin in membrane ruffling (McNiven et al, 2000b), and 2) be localized to, and required for, ECM degradation at invadopodia (Bowden et al, 1999). Interestingly, dynamin is also the target of multiple regulatory inputs such as protein kinase C (Powell et al, 2000), phosphoinositides (Lee et al, 1999;Vallis et al, 1999;Muhlberg and Schmid, 2000), and calcineurin (Liu et al, 1994;Slepnev and De Camilli, 2000). Thus, dynamin and its interacting partners are possible molecular targets for the development of antiinvasive agents.…”
Section: Baldassarre Et Almentioning
confidence: 99%